PENGARUH VARIASI LAMA WAKTU EKSTRAKSI TERHADAP FLAVONOID TOTAL DAUN TAPAK LIMAN (Elephantopus scaber L.) SECARA SPEKTROFOTOMETRI UV-Vis - Feronica, Donna; Susilowati; Saad, Muhammad (Sekolah Tinggi Ilmu Kesehatan Nasional & Pengurus Cabang Ikatan Apoteker Indonesia (IAI) Sukoharjo, 2024)
Elephantopus scaber L. is used as a traditional medicine with flavonoid content. This study aims to determine the total flavonoid content of Elephantopus scaber leaves with varying extraction times of 5 minutes, 10 minutes and 15 minutes. Dried Elephantopus scaber leaves were extracted using water by heating at 95oC for 5, 10 and 15 minutes. Method: Identification of flavonoid compounds in the boiled Elephantopus scaber leaves used the Wilstater method and alkaline reagent test. Total flavonoids were measured using the UV - Vis Spectrophotometry method as quercetin. The research results showed that all test samples contained flavonoids. The highest total flavonoid content of Elephantopus scaber leaves was obtained at the 5th minute, amounting to 94.59 ± 0.1424 mgQE/ 100 ml and the lowest at the 15th minute, amounting to 85.55 ± 0.2376 mgQE/ 100ml. In the